A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil - Schwarzhans, Werner W.; Mincarone, Michael M.; Villarins, Bárbara T. (Zootaxa, 2020)
A new species of Acropomatid fish, Verilus costai sp. nov., is described from a single locality off Belmonte, State of Bahia, Brazil. It resembles Verilus pseudomicrolepis (Schultz, 1940) from the Caribbean Sea. The two are considered vicariant and they are interpreted to be separated from other species of the genus Verilus by (amongst other characters) the presence of fangs on the dentary (vs. only villiform teeth), the anal fin formula (II+9 vs. III+7) and the naked occiput (vs. scaled). However, formal establishment of a separate genus is postponed until a complete phylogenetic review of the family has been performed. Verilus costai can be distinguished from V. pseudomicrolepis by its higher number of gill rakers (27–31 vs. 21–25), lower number of pseudobranchial filaments (15–23 vs. 21–28), shorter snout length (8.2–11.3 vs. 11.3–13.4 % of SL), and more compressed otoliths (OL:OH = 1.3–1.35 vs. 1.35–1.5). In addition, the fossil otolith-based species Verilus mutinensis (Bassoli, 1906) from the late Miocene to middle Pleistocene of the Mediterranean is thought to be related and indicates that in the past this group was more widely distributed than nowadays and comprised more vicariant species.